Effect of tillage system and nitrogen fertilization on the yield of selected spring triticale varieties - admin, Bogusława (Polish Journal of Agronomy, 2021)
The aim of this study was to determine the effect of varying levels of nitrogen fertilization (0, 70, 100 kg ha-1) on yield of spring triticale varieties Milewo, Mazur, Puzon and So- pot under conditions of simplified and traditional tillage. The re- search was conducted in 2017, 2018 and 2020 in Experimental Station of IUNG-PIB in Osiny on soil of good wheat complex. The yield level of spring triticale was affected by the course of weather conditions during the study period, tillage system, nitro- gen doses and variety. Under conditions of more favorable pre- cipitation distribution during the growing season (2017, 2018), grain yields were 32% higher than in 2020. The traditional till- age system ensured higher yields of spring triticale. The applied rate of nitrogen fertilization of 70 kg ha-1 proved to be sufficient for spring triticale yielding under experimental conditions. Under both tillage systems the highest yields were obtained from So- pot. Under conventional tillage Milewo and under reduced tillage Mazur yielded similarly to Sopot. The lowest yield was obtained from Puzon